2014
DOI: 10.1515/jpem-2013-0367
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adenotonsilectomy on ghrelin, leptin, IGF-1 levels and growth parameters in children with adenotonsillar hypertrophy

Abstract: Plasma IGF-1 levels are lower in malnourished children, and plasma ghrelin levels are decreased after acute oral food intake and are increased in cachexia and fasting. Therefore, increased serum IGF-1 levels, height and weight SDS values, and decreased ghrelin levels detected postoperatively are useful parameters that help to monitor the development of children with adequate oral intakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
0
10
0
3
Order By: Relevance
“…However, OSA also predisposes to the worsening of obesity due to daytime sleepiness, decreased physical activity, and neuroendocrine changes, such as resistance to the anorexigenic hormone leptin;405407 data regarding associations between OSA and levels of the orexigenic hormone ghrelin in children are inconsistent 406,407. Treatment of OSA (primarily T&A, but CPAP in one study) may improve leptin and possibly ghrelin levels, although again, data are somewhat contradictory 407.…”
Section: Obstructive Sleep Apnea and Cardiometabolic Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…However, OSA also predisposes to the worsening of obesity due to daytime sleepiness, decreased physical activity, and neuroendocrine changes, such as resistance to the anorexigenic hormone leptin;405407 data regarding associations between OSA and levels of the orexigenic hormone ghrelin in children are inconsistent 406,407. Treatment of OSA (primarily T&A, but CPAP in one study) may improve leptin and possibly ghrelin levels, although again, data are somewhat contradictory 407.…”
Section: Obstructive Sleep Apnea and Cardiometabolic Riskmentioning
confidence: 99%
“…However, OSA also predisposes to the worsening of obesity due to daytime sleepiness, decreased physical activity, and neuroendocrine changes, such as resistance to the anorexigenic hormone leptin;405407 data regarding associations between OSA and levels of the orexigenic hormone ghrelin in children are inconsistent 406,407. Treatment of OSA (primarily T&A, but CPAP in one study) may improve leptin and possibly ghrelin levels, although again, data are somewhat contradictory 407. However, despite these favorable changes, treatment of OSA in children does not necessarily lead to weight loss; as in adults, a number of studies have reported post-T&A weight gain in children and adolescents,408,409 likely due to a reduction in energy expenditure during sleep as well as other hormonal changes.…”
Section: Obstructive Sleep Apnea and Cardiometabolic Riskmentioning
confidence: 99%
“…The overgrown Ad and Tn can induce a developmental disorder in the craniofacial region by obstructing the upper airway and changing respiratory conditions 6 , 7 . It has also been reported that adeno-tonsillar hypertrophy can affect growth in height, weight gain, and cardiopulmonary function 8 , 9 . Recently, it has been shown that adeno-tonsillar hypertrophy is the most common cause of obstructive sleep apnoea (OSA) in children; similarly adeno-tonsillar hypertrophy in adults is one of the reasons of sleep-disordered breathing (SDB), featuring obstructive hypoventilation, snoring, and upper airway narrowing 8 .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that adeno-tonsillar hypertrophy can affect growth in height, weight gain, and cardiopulmonary function 8 , 9 . Recently, it has been shown that adeno-tonsillar hypertrophy is the most common cause of obstructive sleep apnoea (OSA) in children; similarly adeno-tonsillar hypertrophy in adults is one of the reasons of sleep-disordered breathing (SDB), featuring obstructive hypoventilation, snoring, and upper airway narrowing 8 . It has been revealed that a qualitative evaluation of adeno-tonsillar hypertrophy is insufficient for evaluation of the severity of SDB 6 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Leptin has a significant role in food consumption and energy balance regulation (14) as it reduces appetite and increases energy consumption (15). Body mass index (BMI) is significantly correlated with leptin, insulin, and IGF-1 levels (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%